MEMBENTUK PRIBADI MANDIRI DAN BERETIKA MELALUI PROGRAM MAJELIS FAJAR PONDOK PESANTREN AN-NAKHIL DARUNNAJAH 6 - Hasna Gustiani Wahidah; Moechamad Rafi Idzwan Maulana Al Farisi; Muhammad Taufiqur Rohman; Matnur Ritonga (Bajang Institute, 2025)
This research aims to analyze the role of the taklim assembly program at Majelis Fajar Pondok Pesantren Annakhil Darunnajah 6, Mukomuko, Bengkulu, in shaping independent and ethical personalities of students. Using a descriptive qualitative approach, data were collected through observations, in-depth interviews with the management and students, as well as documentation of activities. The research results indicate that through regular activities such as lectures, thematic discussions, worship practices, and skills training, the taklim assembly significantly contributes to fostering personal independence and ethical behavior among students. Supporting factors include the active role of teachers, thematic curriculum, and positive habituation. Challenges found include the lack of digital literacy among the management, limited facilities, and still weak formal evaluation of students' development. This research suggests strengthening management training, utilizing digital media, and evaluation based on independence and ethics indicators.